الضغوط النفسية لدى المعلمين وأثرها على أداءهم المهني في البيئة الصفية: مراجعة منهجية (Comprehensive Journal of Science, 2025)
This research provides a comprehensive systematic review to understand the nature of psychological stress among teachers and its impact on their professional performance in the classroom environment from 2015 to 2025. The significance of the study stems from the increasing challenges teachers faces and the urgent need to support their mental health to enhance educational quality. The research aimed to achieve four main objectives: to identify the sources and patterns of stress, analyze its mechanisms of impact on performance, classify the methodologies and theoretical models used, and uncover knowledge gaps in the field. To achieve this, Thematic Analysis was adopted as the primary methodology, relying on secondary data collection tools through a comprehensive survey of scientific literature. The research population consisted of 215 published studies, from which a sample of 33 geographically and methodologically diverse studies was selected. The collected data were analyzed using descriptive, comparative, and SWOT analysis techniques within the thematic analysis framework. The findings revealed high levels of psychological stress among teachers, which negatively and significantly affects their professional performance, particularly in classroom management and student interaction. The results also indicated that institutional support is a key protective factor, and the relationship between stress and performance is mediated by variables such as motivation and self-esteem. Accordingly, the study recommends adopting sustainable institutional programs to support teacher mental health, reducing administrative burdens, and developing effective classroom management interventions to foster safe and supportive learning environments.
Keywords: Psychological Stress, Professional Performance, Classroom Environment, Teacher Mental Health, Systematic Review